Exploring the Factors Affecting Consumer Purchase Behavior during COVID-19: A Case Study of Techno Products in Dhaka City (Global Journal of Management and Business Research, 2021)
Abstract not found
Keywords: covid-19; consumer behavior; technology industry; economy fluctuation